1992
DOI: 10.1093/genetics/131.2.287
|View full text |Cite
|
Sign up to set email alerts
|

The clr1 locus regulates the expression of the cryptic mating-type loci of fission yeast.

Abstract: The mat2-P and mat3-M loci of fission yeast contain respectively the plus (P) and minus (M) mating-type information in a transcriptionally silent state. That information is transposed from the mat2 or mat3 donor locus via recombination into the expressed mating-type locus (mat1) resulting in switching of the cellular mating type. We have identified a gene, named clr1 (for cryptic loci regulator), whose mutations allow expression of the mat2 and mat3 loci. clr1 mutants undergo aberrant haploid meiosis, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…SHREC also affects nucleosome positioning at a region downstream of the CAS toward mat2P, consistent with the ubiquitous presence of SHREC and its critical role in maintaining TGS across this region. Mutant cells also displayed noticeable differences in MNase digestion pattern at mat3M, the silencing of which requires SHREC components (Ekwall and Ruusala, 1994;Thon et al, 1994;Thon and Klar, 1992). Despite similar overall changes in nucleosome positioning patterns in both mutants, we noticed that chromatin structure was relatively less perturbed in mit1 K587A cells than in clr3 D232N cells (Figure 6E).…”
Section: Shrec Regulates Chromatin Organization At a Heterochromatin Domainmentioning
confidence: 87%
See 1 more Smart Citation
“…SHREC also affects nucleosome positioning at a region downstream of the CAS toward mat2P, consistent with the ubiquitous presence of SHREC and its critical role in maintaining TGS across this region. Mutant cells also displayed noticeable differences in MNase digestion pattern at mat3M, the silencing of which requires SHREC components (Ekwall and Ruusala, 1994;Thon et al, 1994;Thon and Klar, 1992). Despite similar overall changes in nucleosome positioning patterns in both mutants, we noticed that chromatin structure was relatively less perturbed in mit1 K587A cells than in clr3 D232N cells (Figure 6E).…”
Section: Shrec Regulates Chromatin Organization At a Heterochromatin Domainmentioning
confidence: 87%
“…Mass spectrometry analyses identified the 80 kDa polypeptide as Clr3-FLAG, and the 140 and 65 kDa polypeptides respectively as Clr1, a C2H2-type zinc finger protein, and Clr2, a protein with no obvious conserved domain (Figures 1C and S1) (Bjerling et al, 2004). Clr1, Clr2, and Clr3 were identified in screens for factors required for heterochromatic silencing at the mat locus (Ekwall and Ruusala, 1994;Thon et al, 1994;Thon and Klar, 1992), and previous genetic evidence indicates that Clr1 and Clr3 may function jointly in the same pathway (Grewal et al, 1998). We identified the 90 and 170 kDa bands as Ccq1 and SPBP35G2.10, respectively.…”
Section: Purification Of Clr3 and Identification Of Its Interaction Proteinsmentioning
confidence: 99%
“…In this study, we used a highly sensitive reporter system to perform a systematic screen for factors that affect heterochromatic silencing at the silent mat locus. In addition to identifying previously known heterochromatin assembly factors, such as components of the CLRC (Hong et al 2005;Horn et al 2005;Jia et al 2005), HP1 proteins (Thon and Verhein-Hansen 2000;Sadaie et al 2004), SHREC (Thon and Klar 1992;Ekwall and Ruusala 1994;Thon et al 1994;Sugiyama et al 2007), FACT (facilitates chromatin transcription) (Lejeune et al 2007), andFft3 (Strålfors et al 2011;Taneja et al 2017), we identified eight additional factors. Among the newly identified factors were 60S ribosomal proteins (Rpl2102, Rpl39, and Rpl502) and the 19S proteasome regulatory subunit Rpn10.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic screens have proven valuable in identifying factors involved in heterochromatin assembly (Thon and Klar 1992;Ekwall and Ruusala 1994;Thon et al 1994;Bayne et al 2014;Zofall et al 2016;Taneja et al 2017;Jahn et al 2018). To uncover additional factors, we used a sensitized reporter system to screen the S. pombe gene deletion library for factors affecting silencing at the silent mat region.…”
Section: Sensitized Genetic Screen For Heterochromatic Silencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation